2017
DOI: 10.1111/jfb.13324
|View full text |Cite
|
Sign up to set email alerts
|

Histological profiling of gonads depicting protandrous hermaphroditism in Eleutheronema tetradactylum

Abstract: The fourfinger threadfin Eleutheronema tetradactylum is reported as a protandrous hermaphrodite from Australian waters, while being a gonochorist in reports from Singapore and India, with a single report of protandrous hermaphroditism from the latter. Histological analysis of gonads of fish from Indian waters confirms protandrous hermaphroditism in E. tetradactylum. The study was based on 480 fish examined from eight locations along the Indian coast. Mean total length (L ) of male fish was 240 mm with the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 19 publications
(24 reference statements)
1
22
0
Order By: Relevance
“…Following these criteria, and after an extensive review of the literature, functional hermaphroditism was confirmed in 7 orders, 27 families (6% of all fish families) and 94 genera, but without estimation of actual number of species for each type of hermaphroditism (Sadovy de Mitcheson and Liu 2008). More recent studies have investigated the incidence of hermaphroditism in specific groups, e.g., gobies (Cole 2010;Manabe et al 2013;Sunobe et al 2017), serranids (Erisman and Hastings 2011), polynemids (Shihab et al 2017;Butler et al 2018) and sparids (Pla et al 2020) to name some examples, but a global picture, based on current phylogenetic relationships, and with number of species for each major type of hermaphroditism taking into account only confirmed cases is missing. These last points, i.e., based on currently accepted phylogeny and only on confirmed species are very important.…”
Section: Introductionmentioning
confidence: 99%
“…Following these criteria, and after an extensive review of the literature, functional hermaphroditism was confirmed in 7 orders, 27 families (6% of all fish families) and 94 genera, but without estimation of actual number of species for each type of hermaphroditism (Sadovy de Mitcheson and Liu 2008). More recent studies have investigated the incidence of hermaphroditism in specific groups, e.g., gobies (Cole 2010;Manabe et al 2013;Sunobe et al 2017), serranids (Erisman and Hastings 2011), polynemids (Shihab et al 2017;Butler et al 2018) and sparids (Pla et al 2020) to name some examples, but a global picture, based on current phylogenetic relationships, and with number of species for each major type of hermaphroditism taking into account only confirmed cases is missing. These last points, i.e., based on currently accepted phylogeny and only on confirmed species are very important.…”
Section: Introductionmentioning
confidence: 99%
“…(2020), Shihab et al . (2017) and Sparks & Smith (2004; see Table 1 for GenBank Accession Numbers). Collated sequences aligned with MAFFT version 7 (Katoh & Standley, 2013) within Geneious and exported as a PHYLIP‐format file for downstream analyses.…”
Section: Methodsmentioning
confidence: 99%
“…While building the COI dataset and comparing the samples sequenced in this study to sequence data for threadfins databased and distributed through BOLD and/or GenBank, a number of previously generated sequences were found to be misidentified or mislabelled. These came from a variety of published (Betancur‐R et al ., 2013a,b; Chang et al ., 2017; Horne et al ., 2011; Khedkar et al ., 2014; Lakra et al ., 2011; Ribeiro et al ., 2012; Shihab et al ., 2017; Thu et al ., 2019; Qu et al ., 2020; Zhong et al ., 2021) and unpublished works. The recent study by Gopalakrishnan et al .…”
Section: Methodsmentioning
confidence: 99%
“…However, E. tetradactylum is believed to be declining rapidly across much of its tropical Indo-West Pacific range, and is classified as endangered by the IUCN [ 6 ]. Like many fish, E. tetradactylum is a protandrous hermaphrodite that can undergo sex change at different ages [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%